"Religious Nones" in the United Kingdom: How Atheists and Agnostics Think about Religion and Politics. Issue 1 (20th December 2016) - Clements, Ben; Gries, Peter
Abstract: The decline in religious identification and corresponding increase in the unaffiliated has been one of the most important religious changes in the United Kingdom (UK). The emergence of the "religious nones" is the most obvious sign of continuing secularization and the declining social and cultural relevance of religion. Yet while the religiously-unaffiliated often form the plurality — if not sometimes the majority — in many surveys, there has been little scholarly investigation into atheists, agnostics, and others who do not identify with a particular religion. This article uses a 2014 survey of UK adults to examine how those who identify as atheist or agnostic differ from the religiously-affiliated in terms of religiosity, ideology, and policy preferences. Findings reveal secular groups in the UK to be more to the ideological left than the religiously affiliated, and that atheists and agnostics differ from each other and especially the religiously affiliated on public policy.